Endostatin in fibrosis and as a potential candidate of anti-fibrotic therapy. (1st January 2021) - Zhang, Zequn; Liu, Xi; Shen, Zhaolong; Quan, Jun; Lin, Changwei; Li, Xiaorong; Hu, Gui
Abstract: Fibrotic diseases pose significant clinical challenges due to their broadness and complexity. Thus, a better understanding of fibrogenesis and the development of more effective treatments is imperative. Recent evidence suggests a significant antifibrotic potential of an endogenous glycoprotein, endostatin. While endostatin has been widely studied for its role as an anticancer adjuvant by inhibiting tumor angiogenesis, its possible implication in fibrosis remains largely unclear. Here, we review the role of endostatin in various cellular processes and highlight its antifibrotic activity. We hypothesize that endostatin conveys a homeostatic function in the process of fibrosis by regulating (a) TGF-β1 and its downstream signaling; (b) RhoA/ROCK pathway; (c) NF-κB signaling pathway; (d) expression of EGR-1; (e) PDGF/PDGFR pathway; (f) autophagy-related pathways; (g) pathways associated with cell proliferation and apoptosis. Finally, we propose a schematic model of the antifibrotic roles and mechanisms of endostatin; also, we outline future research directions of endostatin and aim to present a potential therapeutic approach for fibrosis.